362 A PhII study of bemcentinib, a first-in-class selective AXL kinase inhibitor, in combination with pembrolizumab in pts with previously-treated advanced NSCLC: Updated clinical & translational analysis. (9th November 2020) - Spicer, James; Helland, Åslaug; Carcereny, Enric; Arriola, Edurne; Gomez, Manuel Dómine; Trigo Perez, Jose Manuel; Thompson, Jonathan; Strauss, James; Ortega Granados, Ana Laura; Felip, Enriqueta; Schmidt, Emmett; Chisamore, Michael; et al.
Abstract : Background: AXL is implicated in resistance to immunotherapy. Bemcentinib (BGB324), a first-in-class, oral, selective and potent AXL kinase inhibitor, enhances checkpoint inhibitor (CPI) efficacy in pre-clinical models through tumor-immune mechanisms. Methods: BGBC008 is a PhII single-arm, 2-stage study with bemcentinib (200 mg/d) and pembrolizumab (200 mg/q3wk) for previously-treated stage IV lung adenocarcinoma comprising 3 cohorts: chemotherapy-pretreated IO-naïve patients (Cohort-A), patients progressing on prior IO therapy (Cohort-B) or chemotherapy/pembrolizumab combination (Cohort-C). Primary endpoint was ORR according to RECIST1.1 with pre-defined criteria to proceed from the first to second stage in each cohort. Secondary endpoints included DCR, PFS, OS and safety. Exploratory endpoints include biomarker analysis and correlation with clinical endpoints, including composite (tumor and immune cell) cAXL score, PD-L1 TPS, and genome-wide mutational and transcriptome analyses. Results: As of July 2020, enrollment in Cohort-A and-B (stage 1) is completed; a total of 66 NSCLC patients were dosed. Cohort-A (n=50) results were previously presented. All Cohort-B1 (n=16) patients received at least one prior line of therapy, the most recent including CPI; 4 patients had 1 and 12 had 2+ prior treatments. Of the Cohort-B1 patients, cAXL status was available for 13 patients: 8 cAXL-positive, 5 cAXL-negative. PD-L1 TPS was available for 13 patients: 5 TPS >50%, 5 TPS 1–49%, and 3 TPS <1%. Of patients who had previously undergone 1 line of CPI therapy (n=4), 75% were cAXL-positive and 25% were not evaluable for cAXL (median TPS of 20%). Patients who had previously undergone 2+ lines of therapy (n=12), 33% were cAXL-positive, 50% cAXL-negative, and 17% not evaluable for cAXL(median TPS of 50%). Of the treated pts, most common TEAEs (>25% of patients) were increased ALT (29%; 10% G3+), AST (29%; 5% G3+), and diarrhoea (29%; 1% G3+). All cases of treatment-related transaminase increase were reversible and managed with concomitant administration of steroids and treatment interruption. Of the 15 radiologically-evaluable patients in Cohort-B1, 1 PR was observed; 6/7 (86%) cAXL-positive patients (1 PR, 5 SD) achieved clinical benefit while none was observed in cAXL negative patients. mPFS was 4.7mo in cAXL-positive and 1.9mo in cAXL-negative patients. Ongoing transcriptional analysis of pre-treatment biopsies revealed a distinct gene profile correlating with clinical benefit from bemcentinib + pembrolizumab combination treatment. Conclusions: Overall, bemcentinib in combination with pembrolizumab was well-tolerated and shows promising clinical activity in AXL-positive immunotherapy refractory disease. Updated survival and translation/biomarker data will be presented. Acknowledgements: The authors would like to thank all patients and their caretakers for participating in this trial. Trial Registration: NCT03184571 Ethics Approval: This study was approved by all relevant institutions, including London Bridge Research Ethics Committee (UK), REC-South East (Norway), Drug Research Ethics Committee of the University Hospital Clinic of Barcelona (Spain), MCW/FH Institutional Review Board #4, Medical College of Wisconsin (USA).